Electric Field Distribution Simulation Of Pt/AlN/Sapphire Resonator For Sensor - Zainol Abidin, Muhammad Hafizuddin; Rosmila Binti Abdul Kahar,; Nur Fatimah Zahra Binti Mohd Khairi,; Muhammad Danial Irfan Bin Mohd Shahar,; Syed Ahmad Hasbi Al Idrus Bin Said Abdul Kadir,; Mirza Basyir Bin Rodhuan, (Enhanced Knowledge in Sciences and Technology, 2023)
This research aims to study the sensitivity of resonator sensors using a Pt/AlN/Sapphire structure. The sapphire substrate is used to increase the sensor's sensitivity, while the high-temperature sensor is made of AlN thin film. The AlN material is chosen for its high acoustic velocity, thermal and chemical stability, and good piezoelectric coupling. The Finite Element Method (FEM) simulation is used to optimize the design and determine the efficiency of the electrical field distribution in the resonator sensor. The outcome of this research will help to advance our understanding of electrical field distribution and the use of sensors and substrates as electrical conductivity mediums in the future. This research opens new possibilities for the use of Pt/AlN/Sapphire in various industries.